Proses Manufaktur Alat Pelepas Seal Suspensi Depan Jenis Telescopic Fork Sepeda Motor - Susilawati - Susilawati; Azhis Sholeh Buchori; Oyok Yudianto (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
One of the most common damages to motorcycles is damage to the seals on the motorcycle suspension, which results in a large amount of oil leakage. To repair the damage a seal removal tool is needed which functions as a Special Service Tool (SST) which is often used in motorcycle workshops. The variety of types and brands of motorcycles, causing motorcycle workshops must have complete equipment, according to the motorcycles brand that is repaired, this results in the expenditure of excess money, especially in the supply of seal removal devices according to the motorcycle brand. The purpose of this research is to create a flexible Telescopic Fork front suspension seal release device, which can be used for all types of motorcycle brands. The method used in this research is tool design, tool manufacturing process, and testing the application of seal removal tools. It is evidenced from the results of the usage test that the resulting seal removal tool can be used for all types of motorcycle brands, this tool can shorten the processing time, and also does not cause new damage to the repaired components. However, it is necessary to examine the application of occupational safety and health to prevent work accidents in the process of making this seal removal device.